Estudio comparativo de las memorias de sostenibilidad GRI y el informe de balance social que reportan las organizaciones nacionales (2009)
A study on the guide G3 by GRI (Global Reporting Initiative) was development in order to assessment the clarity of the principles, orientations and indicators determined by the guidelines. A comparative analysis among the Sustainability Reporting Guidelines and National Responsibility reports was perform for five colombian organizations. The study included the following organizations under evaluation: Cafam (2006), Colsubsidio (2007), Ecopetrol (2007), Fundación Compartir (2006) and Telefónica Colombia (2006). The results obtained for 102 parameters for each report permitted to conclude about the coherence of the parameters relate in the guide G3.